How Do Turnarounds Manage their Mergers and Acquisitions? - Mehta, Aditya Sachin (2014)
This dissertation is focused upon identifying how turnarounds manage their mergers and acquisitions. The initial task involved selecting a sample of 40 firms totally (10 UK public listed firms from 4 industries) and determining which of these firms may be labelled as turnarounds in their industries and which may be labelled as failing firms. As a result there were 8 cases in total that would be evaluated further. (4 turnaround firms and 4 failing firms)